A rare differential diagnosis of air under the diaphragm on abdominal X-ray - Chilaiditi's syndrome in a child with skin wrinkle syndrome - Sreekar Gundapaneni; Debashish Bhattacharya (Wolters Kluwer Medknow Publications, 2022)
Chilaiditi's syndrome is a rare disorder characterized by hepatodiaphragmatic interposition of the intestine. Only 30 cases of Chilaiditi's syndrome in children were reported in the literature and none in a child with skin wrinkle syndrome. Herein, we report a case of Chilaiditi's syndrome in a child with skin wrinkle syndrome.